Development of care skills for the prevention of burnout syndrome in formal caregivers of institutionalized elderly people in Long-Stay Establishments in Montevideo, Uruguay - López Gómez, Alejandro Daniel (2021)
Objective: to describe the socio-occupational profile, as well as the relationship between caregiving skills and chronic work stress in paid formal caregivers of older people who work in long-stay establishments in Montevideo, Uruguay. Method: 213 formal caregivers from 80 establishments participated. A questionnaire of socio-labor data, the Maslach Burnout Inventory and the Nkongho Care Skills Inventory were applied. Results: 95.3% women, mean age 40, 66.2% did not pass lower secondary school and 55.4% did not access any specific training in care. 67.8% show a medium or low level of care ability and 10.2% show a combination of factors associated with chronic work stress. There is a statistically significant relationship between greater caregiving skills and lower risk of chronic work stress. Conclusions: The important daily physical and psycho-affective demand that the care task implies, the low technical and relational training of the staff and the very demanding working conditions, are possible causes of the high presence of chronic work stress in relation to other studies. Ensuring education and training considering gerontological and geriatric aspects is a challenge of the current Care System that could act as a protective factor to avoid stress and humanize care, improving the health of both the elderly and caregivers, as well as the conditions of employability.